Fierce resilience Combatting Workplace Stress One Conversation at a Time - Beltran, Edward (Ascent Audio, 2024)
Discover the science-based secrets to reducing workplace stress, building unwavering resilience, and achieving success through the power of conversation.Technology, isolation, and increasing demands for productivity are making the workplace a hotbed for stress--it's no surprise employees are abandoning traumatic workplaces in unprecedented numbers.Ed Beltran, the CEO of a powerhouse leadership communication company, believes the antidote to stressed-out workplaces starts with conversation.Beltran has developed a science-based model to reduce stress and help people build what he calls fierce resilience. By leveraging the power of conversations, individuals discover their unique stressors, master skills to neutralize stressors, and build unwavering resilience that elevates their emotional well-being.This is no ordinary self-help book. The transformative process of fierce resilience goes well beyond developing mere coping skills. It helps people take control of their emotional health, become more resilient, and build organizations with resilience as a core part of their DNA.
Keywords: Job stress -- Prevention; Psychology, Industrial; Psychologie du travail; Audiobooks; Livres audio